Evaluation and Improvement of Traffic Operation At Kahtan Square inBaghdad city - A. Mansoor Al- Al-Kubaisy, Yousif (Iraqi Journal of Civil Engineering, 2008)
Abstract :The intersections "roundabout" is an important part of the highway system. Theoperational efficiency, capacity, safety and cost of the system depend largely upon itsdesign of intersection "roundabout", especially in urban areas.The objectives of the present study include the analysis, evaluation and improvement theoperation traffic of selected roundabout (Kahtan Square) in Baghdad city by analysis anduse many alternatives to improve the roundabout (Kahtan Square) operation under localexist conditions and to present a best proposal to enhance the performance at the requiredfacility.To achieve these objectives, the traffic volumes data collection and geometric layout forKahtan square that required for the traffic and geometrical analysis were gatheredmanually, while SIDRA traffic program is used for the requirements of traffic analysisprocess.It has been concluded that, fly over at the main path of traffic movement at kahtan square(Baya’a – Yarmok hospital) is the best proposal to improve the capacity and trafficoperation for kahtan square.Keywords: Traffic operation, Round about, Level of service, Capacity